Discipline in Islamic Religious Education: Maintaining Truth Values in the Modern Era - M Mahbubi; Muhammad Yunus (al-Afkar, Journal For Islamic Studies, 2026)
In this rapidly evolving modern era, the primary challenge in Islamic religious education is how to maintain the true values taught in Islam, especially among the younger generation exposed to the influence of globalization, social media, and secular lifestyles. This study aims to analyze the role of discipline in Islamic Religious Education (PAI) at MTs NU Kraksaan in maintaining Islamic values amidst modern progress. This research uses a qualitative approach with a descriptive method, collecting data through in-depth interviews with five Islamic education teachers and direct classroom observations. The results show that discipline in Islamic education not only includes adherence to formal classroom rules but also plays an important role in internalizing religious values in students' daily lives. Discipline is applied through reinforcing classroom rules and instilling religious values in students' routines. Despite challenges such as the influence of social media and limited facilities, consistent discipline implementation positively impacts the strengthening of students' character and morals. The conclusion of this study is that discipline in Islamic education at MTs NU Kraksaan functions as an effective tool to maintain and strengthen the values of Islamic truth among students. This research contributes to the theory of Islamic education by emphasizing the importance of discipline in shaping students' character. The implications of this study highlight the importance of enhancing the role of parents and supporting facilities in the implementation of discipline. Recommendations for future research include exploring the impact of technology on discipline in Islamic education and its application in various madrasahs.